2006
DOI: 10.1002/jcp.20786
|View full text |Cite
|
Sign up to set email alerts
|

A role of novel serpin maspin in tumor progression: The divergence revealed through efforts to converge

Abstract: Maspin, a 42 kDa protein, belongs to the serine protease inhibitor (serpin) superfamily and is more closely related to the ovalbumin-like serpin subfamily (ov-serpins). More than a decade after the discovery of the maspin gene, our pursuit of the molecular mechanisms of maspin revealed a significant divergence of maspin from other serpins. This review article summarizes recent advances in the identification of maspin-binding proteins and the potential underlying molecular mechanisms of maspin in tumor progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 68 publications
0
40
0
Order By: Relevance
“…Maspin is also an important apoptosis-sensitizing factor, making tumor sensitive to drug-induced apoptosis (27,28). It has been shown that Maspin expression was directly correlated with radiochemotherapy response in head and neck squamous cell carcinoma (13,29) and the use of Maspin as a therapeutic target against cancer through the reexpression of Maspin by pharmacologic intervention have been explored (30). In this study, Maspin was downregulated in the radioresistant NPC cells and tissues and its downregulation was associated with NPC radioresistance, which together with reporters suggests that the decrease of Maspin expression in NPC increased its radiation resistance and Maspin might be a biomarker for predicting NPC response to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Maspin is also an important apoptosis-sensitizing factor, making tumor sensitive to drug-induced apoptosis (27,28). It has been shown that Maspin expression was directly correlated with radiochemotherapy response in head and neck squamous cell carcinoma (13,29) and the use of Maspin as a therapeutic target against cancer through the reexpression of Maspin by pharmacologic intervention have been explored (30). In this study, Maspin was downregulated in the radioresistant NPC cells and tissues and its downregulation was associated with NPC radioresistance, which together with reporters suggests that the decrease of Maspin expression in NPC increased its radiation resistance and Maspin might be a biomarker for predicting NPC response to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…24 Loss of maspin can contribute to tumor invasion and metastasis in cancer cells. 25 In addition, maspin can block neovascularization and reduce the density of tumorassociated microvessels in vivo. 26 Thus, we speculated that the altered maspin activation could contribute to the ability of 17-AAG to reverse tumor cell invasion.…”
Section: Itga7mentioning
confidence: 99%
“…Maspin (mammary serpin) is a serine protease inhibitor with tumor suppression activities. Since its discovery in 1994, maspin has been consistently shown to suppress the aggressive tumor phenotypes, inhibiting cell invasion and mobility in vitro and inhibiting tumor growth and metastasis in experimental animal models (32)(33)(34). Maspin is localized both in cytoplasmic and nuclear compartments but may also be secreted.…”
Section: Igfbp-3 and Maspin Synergistically Induced Apoptosis Of Breamentioning
confidence: 99%